2013
DOI: 10.1111/jfbc.12023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Total Phenolic Content and Radical Scavenging Activity of Common Edible Vegetable Oils

Abstract: The study investigates the antioxidant potential of commonly used vegetable oils viz., coconut (CNO), sunflower (SFO), rice bran (RBO), groundnut (GNO), sesame (SESO) and mustard oil (MO), where the oils were extracted with methanol; and these methanolic extracts were used for the antioxidant studies. Fatty acid composition by gas chromatography, physicochemical parameters such as specific gravity, refractive index, acid value, iodine value and peroxide value were also analysed. Total phenolic content (TPC) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 23 publications
3
35
2
1
Order By: Relevance
“…In this case, the highest total phenolics content was determined in nutmeg oil followed by aniseed, coriander, caraway and white mustard oil. Janu et al (2014) reported that the content of phenolic compounds in unrefined mustard oil was 0.56 mg GAE/100 g oil. In turn, Ramadan and Mörsel (2004) analyzed various crude seed oils and determined the total phenolics content in coriander oil at 11 mg caffeic acid equivalents per kg oil equivalents.…”
Section: Total Phenolic Contentmentioning
confidence: 98%
“…In this case, the highest total phenolics content was determined in nutmeg oil followed by aniseed, coriander, caraway and white mustard oil. Janu et al (2014) reported that the content of phenolic compounds in unrefined mustard oil was 0.56 mg GAE/100 g oil. In turn, Ramadan and Mörsel (2004) analyzed various crude seed oils and determined the total phenolics content in coriander oil at 11 mg caffeic acid equivalents per kg oil equivalents.…”
Section: Total Phenolic Contentmentioning
confidence: 98%
“…MCFA's are important in human diet as they are reported to be inert source of energy that the human body finds it easier to metabolize and do not require energy for absorption, utilization and storage (Hiroyuki et al 2008). Phenolic compounds namely, ferulicacid, vanillic acid, syringicacid, gallocatechin gallate, p-coumaric acid, sinapic acid and cinnamic acid, were identified from the methanolic extract of CNO (Janu et al 2014;Marina et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Esse resultado demonstra que o processo de aquecimento do óleo leva ao consumo dos antioxidantes, com o objetivo de inibir a formação dos produtos da oxidação. (28) O consumo de alimentos preparados em óleos ou gorduras processados, contendo produtos oxidados pode trazer prejuízos à saúde. Esses produtos podem provocar ligações cruzadas nas lipoproteínas de baixa densidade, causando acúmulo de colesterol nos vasos sanguíneos.…”
Section: Discussionunclassified